Analisis Faktor-Faktor yang mempengaruhi produktivitas kerja pada UMKM Batik Tulis Seruni Purwodadi - Dhita Novia Ramadhani; Sutrisno Sutrisno; Noni Setyorini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of the variables of morale, work environment, work skills, teamwork, work climate on the work productivity of UMKM Batik Tulis Seruni Purwodadi employees. The population in this study was 150 employees, the sample that was determined in this study was 109 employees using a saturated sample. This study uses SPSS to answer the main facts by using a list of questionnaires that have been answered by respondents. The findings of this study are that work enthusiasm has a positive and significant effect on the work productivity of UMKM Batik Tulis Seruni Purwodadi employees, the work environment has a positive and significant effect on the work productivity of UMKM Batik Tulis Seruni Purwodadi employees, work skills have a positive and significant effect on the work productivity of UMKM Batik Tulis Seruni employees Purwodadi, teamwork has a positive and significant effect on the work productivity of UMKM Batik Tulis Seruni Purwodadi, the work climate has a positive and significant effect on the work productivity of UMKM employees Batik Tulis Seruni Purwodadi